Phenytoin Administration Following Early Postoperative Seizure After Brain Tumor Surgery - Nugroho, Andy; Bisri, Dewi Yulianti; Rachman, Iwan Abdul (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Early postoperative seizures (EPS), defined as seizures occurring within seven days following brain surgery, are a common and serious complication, particularly in patients with high-grade gliomas. EPS can prolong hospitalization, impair neurological recovery, and increase the risk of further brain injury. The optimal prophylactic strategy for seizure prevention remains controversial, especially in settings where access to second-generation antiepileptic drugs is limited.Case: A 53-year-old female presented with progressive headaches and was diagnosed with a supratentorial intra-axial tumour consistent with high-grade glioma. She underwent subtotal tumour resection. Four hours postoperatively, the patient developed two episodes of generalized seizures. Immediate management included intravenous administration of midazolam, endotracheal intubation, and phenytoin administration. Diagnostic evaluations excluded metabolic or infectious causes. Near-infrared spectroscopy (NIRS) monitoring indicated stable cerebral oxygenation throughout the postoperative course. The patient experienced no further seizures and demonstrated full neurological recovery. Oral phenytoin was continued for 21 days.Discussion: EPS are associated with multiple risk factors, including tumour location, size, and incomplete resection. In this case, the tumour’s frontal and parietal lobe involvement, large volume, and subtotal excision likely contributed to seizure onset. Phenytoin, despite being a first-generation antiepileptic drug, proved effective in managing EPS and preventing recurrence in the absence of levetiracetam. NIRS served as a useful non-invasive adjunct to monitor cerebral oxygenation after a seizure.Conclusion: Effective early recognition and treatment of EPS are critical in preventing secondary neurological complications. In resource-limited settings, phenytoin remains a viable monotherapy for seizure control post-craniotomy. Individualized, protocol-driven management strategies, supported by neuromonitoring tools such as NIRS, can optimize outcomes in brain tumor surgery.